(untitled) (Swiss Medical Weekly, 2012)
The anti-inflammatory actions of therapeutic glucocorticoids are well established and these drugs are widely used to treat a variety of inflammatory conditions. It is also clear that endogenously synthesised glucocorticoids have an important role in regulating inflammatory responses. Traditionally, our understanding of the effects of endogenous glucocorticoids has been based on the levels of glucocorticoids within the circulation. These levels are controlled by the hypothalamic-pituitary-adrenal axis. However, more recently it has been established that the local level of glucocorticoids is of potential importance. Situations where the local level of glucocorticoids may differ from the level in the circulation are illustrated in this review. In addition, the mechanisms regulating local glucocorticoid levels and actions are identified. Increasingly, it will be important to understand how the levels of glucocorticoids within the circulation and within the tissues are regulated in a coordinated manner.